Immigration and European integration. Towards fortress Europe. 2nd ed. - Geddes, Anthony (Manchester, 2008)
"Migration is at the heart of the contemporary European Union. This new edition addresses three key questions that underpin EU responses to migration policy. First, what role does the EU play in the regulation of migration? Second, how and why have EU measures developed to promote the integration of migrants and their descendants? Third, what impact do EU measures on migration and asylum have on new member states and non-member states? The updated edition covers important recent developments, addressing new migration flows and the external dimension of EU action on migration and asylum and placing in all these in the context of a 'wider' Europe. Andrew Geddes provides comprehensive analysis of the EU's free movement framework, of the development of co-operation on immigration and asylum policy, of the mobilisation by groups seeking to represent migrants' interests in EU decision-making, the interface between migration, welfare and the EU's social dimension, and the impact of enlargement on migration and asylum. This innovative and original analysis of the European dimension of immigration policy is essential reading for scholars of European integration, the politics of immigration and the prospects for new patterns of migrant inclusion at member state and EU level."